CASE REPORTSEmergency repair of the aortic arch in a premature newborn - Haponiuk, Ireneusz; Chojnicki, Maciej; Jaworski, Radoslaw; Kwasniak, Ewelina; Juscinski, Jacek; Steffens, Mariusz; Szofer-Sendrowska, Aneta; Domzalska-Popadiuk, Iwona; Gierat-Haponiuk, Katarzyna; Zielinski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
We present a case of a successful two-step surgical treatment of a low body weight premature newborn (weight of 1140 g) who underwent emergency surgical repair of aortic coarctation and closure of ventricular and atrial septal defects at the age of 7 months. In the end, the multi-staged strategy comprising the emergency repair of the coarctation and the subsequent intracardiac correction in the premature newborn turned out to be safe and effective. This may serve as encouragement to employ similar promising treatment methods for borderline low body mass newborns in the future.